2014
DOI: 10.1186/s12983-014-0056-y
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric prey responses to lethal top-predator control: predator manipulation experiments

Abstract: Introduction: Many prey species around the world are suffering declines due to a variety of interacting causes such as land use change, climate change, invasive species and novel disease. Recent studies on the ecological roles of top-predators have suggested that lethal top-predator control by humans (typically undertaken to protect livestock or managed game from predation) is an indirect additional cause of prey declines through trophic cascade effects. Such studies have prompted calls to prohibit lethal top-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 92 publications
(237 reference statements)
3
44
0
Order By: Relevance
“…Mixed relationships between dingoes and macropods have been found in temperate areas over longer timeframes (Claridge et al 2010;Arthur et al 2013). These studies support observations described here and elsewhere which report that dingoes can limit kangaroo populations in open areas under certain conditions (Choquenot and Forsyth 2013;Allen et al 2014a;Prowse et al 2014), and that the greatest densities of kangaroos occur in places relatively devoid of dingoes (Caughley et al 1980;Pople et al 2000;Letnic and Crowther 2013. Annual kangaroo abundance estimates for the NE region would have been immeasurably useful to our study, though none are available because cattle producers there have not considered kangaroo abundances great enough to warrant establishment of a harvesting industry -the ultimate purpose behind kangaroo density surveys (DEH 2008). However, anecdotal reports claim that 'most of the kangaroos in NSA are in the NW because they bait dingoes there', concurring with several geographically-limited studies (Caughley et al 1980;Pople et al 2000;Newsome et al 2001;Fillios et al 2010;Letnic and Crowther 2013;Allen et al 2014a) that report kangaroo abundances to be persistently low in the NE region.…”
Section: Accepted M Manuscriptsupporting
confidence: 88%
See 3 more Smart Citations
“…Mixed relationships between dingoes and macropods have been found in temperate areas over longer timeframes (Claridge et al 2010;Arthur et al 2013). These studies support observations described here and elsewhere which report that dingoes can limit kangaroo populations in open areas under certain conditions (Choquenot and Forsyth 2013;Allen et al 2014a;Prowse et al 2014), and that the greatest densities of kangaroos occur in places relatively devoid of dingoes (Caughley et al 1980;Pople et al 2000;Letnic and Crowther 2013. Annual kangaroo abundance estimates for the NE region would have been immeasurably useful to our study, though none are available because cattle producers there have not considered kangaroo abundances great enough to warrant establishment of a harvesting industry -the ultimate purpose behind kangaroo density surveys (DEH 2008). However, anecdotal reports claim that 'most of the kangaroos in NSA are in the NW because they bait dingoes there', concurring with several geographically-limited studies (Caughley et al 1980;Pople et al 2000;Newsome et al 2001;Fillios et al 2010;Letnic and Crowther 2013;Allen et al 2014a) that report kangaroo abundances to be persistently low in the NE region.…”
Section: Accepted M Manuscriptsupporting
confidence: 88%
“…Annual rainfall was calculated for the calendar year, January to December. Detailed descriptions of NSA, along with background information on contemporary dingo, kangaroo and cattle management practices are not described here, but can be found elsewhere (Wallis 1997;DEH 2008;Allen 2012;Allen et al 2013a;Allen et al 2014a). Although other means of lethal dingo control (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, several studies using strongly-inferential methods demonstrate that such top-down effects do not always occur, or if they do, they are far weaker than bottom-up processes (e.g. Gasaway et al, 1983;Boertje et al, 1996;Hayes et al, 2003;Vucetich and Peterson, 2004;Vucetich et al, 2005; Giordano, 2013;Marshall et al, 2013;Allen et al, 2014b;Ford et al, 2015a;Sivy, 2015; see also Schmitz et al, 2000;Bowyer et al, 2005;Sergio et al, 2008;McCoy et al, 2012;White, 2013;McPeek, 2014;Kuijper et al, 2017). Ford and Goheen (2015) showed that of five strongly-inferential experiments investigating large carnivores' roles, only two found evidence supporting the TCH.…”
Section: Introductionmentioning
confidence: 99%